The microbiology of acute diarrhoeal disease in the eastern province of saudi arabia - El-Freihi, H.; Twum-Danso, K.; Sohaibani, M.; Bellah, H.; EL-Mouzan, M.; Sama, K. (My University, 2013)
A prospective study of acute diarrhoeal diseases in the Eastern Province of Saudi Arabia was carried out over a 19-month period to determine aetiology, risk factors and other epidemiological characteristics. Of the 853 subjects studied, 344 were cases and 509 controls. More cases were seen in children than in adults. Enteric pathogens were detected in 49% of the cases, but none in the controls. Of the pathogens, 68% were bacterial with Salmonella (34%) and Shigella species (14.7%) being the most common; Campylobacter jejuni emerged as an important cause especially in adults. Contrary to most reports, rotaviruses were responsible for only 11.5% of the cases in children
Keywords: Diarrhea ; Saudi Arabia ; Human ; Bacteriological investigation ; Microbiological investigation ; Statistical study ; Asia ; Digestive diseases ; Intestinal disease